Methoxyflurane Analgesia in Adult Patients in the Emergency Department: A Subgroup Analysis of a Randomized, Double-blind, Placebo-controlled Study (STOP!). Issue 11 (November 2016) - Coffey, Frank; Dissmann, Patrick; Mirza, Kazim; Lomax, Mark
Abstract Introduction Acute pain remains highly prevalent in the Emergency Department (ED) setting. This double-blind, randomized, placebo-controlled UK study investigated the efficacy and safety of low-dose methoxyflurane analgesia for the treatment of acute pain in the ED in the adult population of the STOP! trial. Methods Patients presenting to the ED requiring analgesia for acute pain (pain score of 4–7 on the Numerical Rating Scale) due to minor trauma were randomized in a 1:1 ratio to receive methoxyflurane (up to 6 mL) or placebo (normal saline), both via a Penthrox® (Medical Developments International Limited, Scoresby, Australia) inhaler. Rescue medication (paracetamol/opioids) was available immediately upon request. Change from baseline in visual analog scale (VAS) pain intensity was the primary endpoint. Results 300 adult and adolescent patients were randomized; data are presented for the adult subgroup (N = 204). Mean baseline VAS pain score was 66 mm in both groups. The mean change from baseline to 5, 10, 15 and 20 min was greater for methoxyflurane (−20.7, −27.4, −33.3 and −34.8 mm, respectively) than placebo (−8.0, −11.1, −12.3 and −15.2 mm, respectively). The primary analysis showed a highly significant treatment effect overall across all four time points (−17.4 mm; 95% confidence interval: −22.3 to −12.5 mm;p < 0.0001). Median time to first pain relief was 5 min with methoxyflurane [versus 20 min with placebo; (hazard ratio: 2.32; 95% CI: 1.63, 3.30;p < 0.0001)]; 79.4% of methoxyflurane-treated patients experienced pain relief within 1–10 inhalations. 22.8% of placebo-treated patients requested rescue medication within 20 min compared with 2.0% of methoxyflurane-treated patients (p = 0.0003). Methoxyflurane treatment was rated 'Excellent', 'Very Good' or 'Good' by 77.6% of patients, 74.5% of physicians and 72.5% of nurses. Treatment-related adverse events (mostly dizziness/headache) were reported by 42.2% of patients receiving methoxyflurane and 14.9% of patients receiving placebo; none caused withdrawal and the majority were mild and transient. Conclusion The results of this study support the evidence from previous trials that low-dose methoxyflurane administered via the Penthrox inhaler is a well-tolerated, efficacious and rapid-acting analgesic. Funding Medical Developments International (MDI) Limited and Mundipharma Research GmbH & Co.KG. Trial registration Clinicaltrials.gov identifier: NCT01420159, EudraCT number: 2011-000338-12.